Pancreatic mucinous cystic neoplasm in a transgender patient - Foster, Deshka (World J Surg Oncol, 2015)
BACKGROUND: Cystic pancreatic lesions are increasingly more frequent detected clinical entities. Mucinous cystic neoplasm (MCN) is a hormone-related pancreatic tumor (HRTP) with a strong predominance in young and middle-aged females. CASE PRESENTATION: Here, we present the case of a 31-year-old surgically transgendered female-to-male patient with a history of alcoholic pancreatitis, on chronic testosterone therapy. He was found to have a pancreatic MCN and underwent distal pancreatectomy and splenectomy. CONCLUSION: To our knowledge, this is the first reported case of a transgender patient with a history of hormone replacement therapy (HRT) and pancreatic MCN. We consider possible mechanisms for the pathogenesis to explain this patient’s neoplasm.